2013
DOI: 10.1083/jcb.201304174
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule severing by the katanin complex is activated by PPFR-1–dependent MEI-1 dephosphorylation

Abstract: Dephosphorylation of MEI-1 activates katanin during meiosis, whereas ubiquitin-mediated degradation of both MEI-1 and its activator PPFR-1 ensure efficient katanin inactivation during mitosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 33 publications
3
35
0
Order By: Relevance
“…Close inspection of the images from prior work showed that Drosophila katanin p60 was diffusely localized to the entire chromosome but was not specifically at the kinetochores (Zhang et al, 2007). (2) Some types of katanin p60 have been shown to be regulated by kinase activity (Gomes et al, 2013;Quintin, Mains, Zinke, & Hyman, 2003), specifically Aurora B kinase (Loughlin et al, 2011). (2) Some types of katanin p60 have been shown to be regulated by kinase activity (Gomes et al, 2013;Quintin, Mains, Zinke, & Hyman, 2003), specifically Aurora B kinase (Loughlin et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Close inspection of the images from prior work showed that Drosophila katanin p60 was diffusely localized to the entire chromosome but was not specifically at the kinetochores (Zhang et al, 2007). (2) Some types of katanin p60 have been shown to be regulated by kinase activity (Gomes et al, 2013;Quintin, Mains, Zinke, & Hyman, 2003), specifically Aurora B kinase (Loughlin et al, 2011). (2) Some types of katanin p60 have been shown to be regulated by kinase activity (Gomes et al, 2013;Quintin, Mains, Zinke, & Hyman, 2003), specifically Aurora B kinase (Loughlin et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we reasoned that localizing katanin p60 to the kinetochores, where it could directly affect microtubule attachment to the chromosomes, could serve as a proofof-concept. (2) Some types of katanin p60 have been shown to be regulated by kinase activity (Gomes et al, 2013;Quintin, Mains, Zinke, & Hyman, 2003), specifically Aurora B kinase (Loughlin et al, 2011). The kinetochore is a location with high levels of Aurora B kinase activity (Tanaka et al, 2002;Cheeseman et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Contractile ring dynamics during meiosis I were more normal after mei-1 RNAi knockdown, but the furrows nevertheless often regressed and polar body extrusion usually failed. Previous studies have shown that partial loss of function mutations in mei-1 result in abnormally large second polar bodies that are produced after meiosis II, as a result of decreased microtubule severing that is required for complete disassembly of the oocyte meiosis II spindle (42, 43). Our results provide the first systematic examination of polar body extrusion during meiosis I after depletion of katanin/MEI-1, and it is possible that the late failures in polar body cytokinesis that we observed also reflect a requirement for microtubule severing.…”
Section: Discussionmentioning
confidence: 99%
“…Here we report our use of fluorescent protein fusions and live cell imaging to characterize polar body extrusion during meiosis I in mutants lacking the function of CLS-2, KLP-18 or MEI-1. Previous studies indicate that both CLS-2 and MEI-1 are involved in polar body extrusion, with oocytes lacking CLS-2 frequently failing to extrude polar bodies (27, 30, 41), and oocytes lacking MEI-1 forming very large polar bodies (16, 17, 42, 43). Furthermore, klp-18 mutants sometimes lack an oocyte pronucleus, suggesting that all oocyte chromosomes can be extruded (34).…”
Section: Introductionmentioning
confidence: 99%
“…In Xenopus, phosphorylation of p60 on Ser 131 inhibits its activity (Loughlin et al, 2011;Whitehead et al, 2013). In C. elegans, p60 is also regulated by phosphorylation; an MBK-2 kinase-dependent phosphorylation leads to an inactivation of p60 and its subsequent ubiquitination and degradation (Stitzel et al, 2006;Lu and Mains, 2007;Johnson et al, 2009), while dephosphorylation by PP4 phosphatase activates p60 (Han et al, 2009;Gomes et al, 2013). Destruction of katanin by ubiquitination-dependent degradation also takes place in mammalian cells (Cummings et al, 2009;Yang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%